Death: A Philosophical Perspective on the Legal Definitions - William C. Charron (Washington University Law Quarterly, 1975)
In light of semantic and ethical requirements developed from a consideration of the problems and interests surrounding the definitional debate, the Article evaluates the various definitions of death recently set forth by state legislatures, courts, and professional organizations, all of which equate human death with a physiological state of one kind or another. In turn, a definition of human death on a psychological plane that identifies death with the permanent loss of all consciousness is recommended for public acceptance. Accordingly, certain physiological states, such as the functional disintegration of the brain (or of the brain cortex alone), become empirically established indicators (diagnostic criteria) of the occurrence of human death in the psychological sense.
Keywords: Dead bodies; Medical jurisprudence